Analisis Lima Prinsip GCG Dalam Implementasi Sifat Nabi Muhammad SAW - Filail, Suqa Annisa; Dharmayanti , Sinta Putri; Djasuli , Mohamad (CV. ITTC INDONESIA, 2022)
There are five principles of Good Corporate Governance, but the principles of GCG are also inseparable from the values ​​taught in Islam, especially those presented by the Prophet Muhammad SAW. The study was carried out qualitatively, describing the moral example of the Prophet Muhammad SAW with the principles of good corporate governance. The findings of this article illustrate the exemplary morality of the Prophet Muhammad, among others. Shiddiq, Amanah, Tabligh and Fathanah can be found in GCG principles. The author links these GCG principles with the moral example of the Prophet Muhammad SAW, because they are interrelated and emphasize that ethics applied in life cannot be separated from religious values. The greedy nature of most people must be controlled from a religious point of view, so that they are not always satisfied with worldly life. The Prophet's moral example is found in good corporate governance, first, Shiddiq, namely the nature of the prophet, which means honesty in deeds and words including transparency and independence, as good corporate governance. Trust implies responsibility and accountability, where a person can be trusted and is responsible for all actions taken. Tabligh is featured in Good Corporate Governance Transparency. The essence of Fathanah is embodied in justice which includes precision and prudence. The exemplary character of the Prophet Muhammad SAW is interrelated with GCG so that companies can emulate the example of the Prophet in business management so that companies can achieve even better results